2000
DOI: 10.1046/j.1365-3083.2000.00703.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunological Cytokine Correlates of Protective Immunity and Pathogenesis in Leprosy

Abstract: The in vitro production of interferon (IFN)-g, interleukin (IL)-5, tumour necrosis factor (TNF)-a and IL-10 by blood mononuclear cells in response to whole Mycobacterium leprae and polyclonal stimulii of 23 individuals, representing a variety of conditions in relation to exposure/susceptibility to M. leprae, was assayed. In most cases, healthy household contacts of newly diagnosed multibacillary leprosy patients, designated exposed household contacts (EC), showed low-to-undetectable in vitro IFN-g production i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
26
0
6

Year Published

2001
2001
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 40 publications
3
26
0
6
Order By: Relevance
“…A higher tumor necrosis factor-a (TNF-a)/IL-10 ratio was correlated with a better prognosis in terms of clinical outcome of leprosy household contacts. 9 Besides, it has been suggested that IL-10 is enhanced in the MB form of the disease. 10 The IL-10 gene is located on chromosome 1q32 and microsatellites and single nucleotide polymorphisms (SNPs) are arranged to form haplotypes that are associated with levels of IL-10 production.…”
Section: Introductionmentioning
confidence: 99%
“…A higher tumor necrosis factor-a (TNF-a)/IL-10 ratio was correlated with a better prognosis in terms of clinical outcome of leprosy household contacts. 9 Besides, it has been suggested that IL-10 is enhanced in the MB form of the disease. 10 The IL-10 gene is located on chromosome 1q32 and microsatellites and single nucleotide polymorphisms (SNPs) are arranged to form haplotypes that are associated with levels of IL-10 production.…”
Section: Introductionmentioning
confidence: 99%
“…As a first approach, we compared the level of TNF-α secretion induced in these cells after phagocytosis of Mycobacterium leprae, the causative agent of leprosy, and M. bovis BCG, an attenuated strain used as a vaccine against leprosy and tuberculosis. Blood mononuclear cells of both normal individuals or leprosy patients secrete TNF-α in response to M. leprae and BCG (Santos et al 1993, Suzuki et al 1993, Lima et al 2000. Besides its role in the differentiation of Th1 cells, TNF-α is involved in the formation of granulomas that play an essential role in preventing the extension and dissemination of mycobacterial infections (Kindler et al 1989).…”
mentioning
confidence: 99%
“…Multibacillary leprosy is characterized by high bacillary load and many skin lesions. Therefore, the untreated multibacillary patients are the main source of leprosy transmission [7][8][9][10][11]. Th2 cytokine levels such as IL-4, IL-5, and IL-10 that are characteristic of lepromatous or multibacillary patients, are elevated in those patients.…”
Section: Introductionmentioning
confidence: 99%
“…Th2 cytokine levels such as IL-4, IL-5, and IL-10 that are characteristic of lepromatous or multibacillary patients, are elevated in those patients. While the level of Th1 cytokines is low, including IFNγ [8,9,12,13]. Interferon-γ is a major macrophage-activating cytokine and has a role in natural defense and cellular immunity against intracellular microbes such as M. leprae.…”
Section: Introductionmentioning
confidence: 99%